Effects of lower back foam rolling on the pressure pain threshold and the range of motion of the lumbar spine in healthy individuals - Fijavž, Julia; Frangež, Maja; Vauhnik, Renata (Frontiers in Physiology, 2024)
The aim of this study was to determine the short-and long-term effects of foam rolling (FR) on the pressure pain threshold and the range of motion of the lumbar spine in healthy subjects. 43 healthy subjects without back problems were randomly assigned to an experimental group (EG) or a control group (CG). The subjects in the EG underwent a 4-week FR program (12 sessions). The subjects in the CG received no intervention. Range of motion was measured using the modified-modified Schober test for flexion and fingertip-to-floor distance for lateral flexion. The pressure pain threshold was measured with a hand-held pressure algometer. The measurements were taken before and after the first FR, after the 4-week program and at the 1-, 3-and 6-month follow-up. The significance level was set at p ≤ 0.05 and the desired power of the test was 92%.We found an improvement in flexion (p = 0.03) and lateral flexion (p < 0.001) in the EG after the first FR and recorded a significant improvement in all measured variables (flexion, lateral flexion and algometry: p < 0.001) at the end of the entire 4-week program. The effects were noticeable up to 6 months after the end of the program (p ≤ 0.03) and were statistically significantly better than in the CG (p ≤ 0.04). The calculated Cohen's d value was 1.15 for flexion, 1.06 for lateral flexion and 0.98 for algometry, which represents a large effect size. FR improves the pressure pain threshold and mobility of the lumbar spine in healthy subjects. The effects are noticeable at least 6 months after the end of an FR program.